A feasibility study for a randomised controlled trial of the Positive Reappraisal Coping Intervention, a novel supportive technique for recurrent miscarriage - Bailey, Sarah J.; Bailey, Christopher; Boivin, Jacky; Cheong, Ying; Reading, Isabel; Macklon, Nick (BMJ Publishing Group, 2015)
Introduction: Recurrent miscarriage (RM) is diagnosed when a woman has had three or more miscarriages. Increased levels of distress and anxiety are common during the waiting period of any subsequent pregnancies, posing a significant threat to psychological well-being. However, only limited support and therapy are available for these women, and many are left to cope alone. The Positive Reappraisal Coping Intervention (PRCI) is a novel self-administered supportive technique which has been shown to be effective in patients awaiting the outcome of in vitro fertilisation treatment. The primary objective of this study is to assess the feasibility and effectiveness of the PRCI in improving quality of life in the difficult waiting period which women with previous RM endure before an ongoing pregnancy can be confirmed.